Evaluation of high‐level clouds in cloud resolving model simulations with ARM and KWAJEX observations. (5th November 2015) - Liu, Zheng; Muhlbauer, Andreas; Ackerman, Thomas
Abstract: In this study, we evaluate high‐level clouds in a cloud resolving model during two convective cases, ARM9707 and KWAJEX. The simulated joint histograms of cloud occurrence and radar reflectivity compare well with cloud radar and satellite observations when using a two‐moment microphysics scheme. However, simulations performed with a single moment microphysical scheme exhibit low biases of approximately 20 dB. During convective events, two‐moment microphysical overestimate the amount of high‐level cloud and one‐moment microphysics precipitate too readily and underestimate the amount and height of high‐level cloud. For ARM9707, persistent large positive biases in high‐level cloud are found, which are not sensitive to changes in ice particle fall velocity and ice nuclei number concentration in the two‐moment microphysics. These biases are caused by biases in large‐scale forcing and maintained by the periodic lateral boundary conditions. The combined effects include significant biases in high‐level cloud amount, radiation, and high sensitivity of cloud amount to nudging time scale in both convective cases. The high sensitivity of high‐level cloud amount to the thermodynamic nudging time scale suggests that thermodynamic nudging can be a powerful "tuning" parameter for the simulated cloud and radiation but should be applied with caution. The role of the periodic lateral boundary conditions in reinforcing the biases in cloud and radiation suggests that reducing the uncertainty in the large‐scale forcing in high levels is important for similar convective cases and has far reaching implications for simulating high‐level clouds in super‐parameterized global climate models such as the multiscale modeling framework. Key Points: Two‐moment microphysics improves simulated radar reflectivity histograms Simulated high cloud amount is not sensitive to uncertainties in tested ice microphysics Forcing uncertainties and periodic lateral BC lead to bias in high cloud amount